Social support and mental health among female employees: the moderating effect of age - Hamzah, Hazalizah; Ramlee, Fatanah; Perveen, Asma; Mustapha, Roslinda; Zulkifli, Syara Shazanna (International Journal of Public Health Science (IJPHS), 2023)
The association between social support and mental health at work has been widely established; nevertheless, notably among working women, the significance of age in that relationship remains controversial. This research used age as a moderator to determine mental health from social support. The Interpersonal Support Evaluation List–12 (ISEL-12) and the Mental Health Inventory–18 (MHI-18) was answered by 100 working women (Mage=41.20; SDage=9.80). A significant association between social support and mental health were reported but not between age and mental health. Age moderated the connection between social support and mental health. Younger women demonstrated greater mental health than older women in low-social support environments. With increasing social support, older working women reported better mental health. The findings of this study can be implemented by companies to develop and implement social support methods and policies to improve overall mental health in the workplace.